An Experimental Model of Bronchopulmonary Dysplasia Features Long-Term Retinal and Pulmonary Defects but Not Sustained Lung Inflammation - Wickramasinghe, Lakshanie C.; van Wijngaarden, Peter; Johnson, Chad; Tsantikos, Evelyn; Hibbs, Margaret L. (Frontiers in Pediatrics, 2021)
Bronchopulmonary dysplasia (BPD) is a severe lung disease that affects preterm infants receiving oxygen therapy. No standardized, clinically-relevant BPD model exists, hampering efforts to understand and treat this disease. This study aimed to evaluate and confirm a candidate model of acute and chronic BPD, based on exposure of neonatal mice to a high oxygen environment during key lung developmental stages affected in preterm infants with BPD. Neonatal C57BL/6 mouse pups were exposed to 75% oxygen from postnatal day (PN)-1 for 5, 8 or 14 days, and their lungs were examined at PN14 and PN40. While all mice showed some degree of lung damage, mice exposed to hyperoxia for 8 or 14 days exhibited the greatest septal wall thickening and airspace enlargement. Furthermore, when assessed at PN40, mice exposed for 8 or 14 days to supplemental oxygen exhibited augmented septal wall thickness and emphysema, with the severity increased with the longer exposure, which translated into a decline in respiratory function at PN80 in the 14-day model. In addition to this, mice exposed to hyperoxia for 8 days showed significant expansion of alveolar epithelial type II cells as well as the greatest fibrosis when assessed at PN40 suggesting a healing response, which was not seen in mice exposed to high oxygen for a longer period. While evidence of lung inflammation was apparent at PN14, chronic inflammation was absent from all three models. Finally, exposure to high oxygen for 14 days also induced concurrent outer retinal degeneration. This study shows that early postnatal exposure to high oxygen generates hallmark acute and chronic pathologies in mice that highlights its use as a translational model of BPD.